Carbon Sequestration in Peatlands: Using Environmental Proxies to Understand the Impact of a Changing Climate on Global Carbon Storage: Using Environmental Proxies to Understand the Impact of a Changing Climate on Global Carbon Storage (University of Denver Undergraduate Research Journal, 2024)
Peatlands are a type of terrestrial wetland ecosystem in which consistently waterlogged conditions prevent the decomposition of organic matter. These conditions allow for sequestered carbon in plant matter to remain stored in the soil to such a great degree that peatlands store more carbon than all other vegetation types in the world combined. By inhibiting decomposition, the composition of water-rich peat soil remains representative of the environmental conditions during the period in which the peat was formed. The collected peat samples can then be utilized as environmental proxies to determine historical temperature, moisture, and carbon content and extrapolated to predict the future capacity of carbon sequestration in the context of a changing climate.The peat samples in this research were collected during the fall of 2020 in the Echo Lake Fen of Grand Mesa, Colorado, and analyzed using humification analysis to determine changes in organic content over time. This research examines over 200 cm of peat from the Echo Lake Fen, dating back over 8,000 years. Each sample was divided into smaller sections to represent shorter periods of time and tested to determine organic matter content. Results suggest that warmer climates lower the water table of a peatland and expose plant matter to oxygen, allowing plants to decay and release carbon into the atmosphere. This raises concerns about the amount of carbon that could be released into the atmosphere in the future as the climate is predicted to get hotter and drier.Understanding that carbon, as a greenhouse gas, exacerbates already rising global temperatures and increases the rate of plant decomposition is important in predicting how the loss of peatlands would impact future climate conditions. Peat soils contain more than 600 gigatons of carbon worldwide, which represents up to 44% of all soil carbon. Thus, it is essential that efforts to preserve and restore peatlands are prioritized to minimize the amount of carbon in the atmosphere. This research serves as strong evidence for investing in peatland conservation and restoration.